The Implementation of the Singing Method to Enhance Early Reading Skills of Children Aged 4–5 Years at PAUD Dakar - Siti Hamsanah; Novita Sari; Sanin Sudrajat; Mahsiani Mina Laili; Tito Parta Wibowo (CV. Creative Tugu Pena, 2026)
This research was conducted at DAKAR Early Childhood Education (PAUD) in Cilegon City, Banten, with the aim of determining the application of the singing method to improve early reading skills in children aged 4-5 years. Initial observations revealed that during learning activities, only a few children recognized letters and words, while the majority did not yet. Therefore, to assess the reading abilities of these young children, it is necessary to develop more engaging and effective learning methods to improve their understanding of letters during the early reading stage, including singing while introducing letters and words. The research methodology was descriptive qualitative, as the researcher aimed to describe or elaborate on an event by conducting in-depth research related to the research topic. The results of the study, through data collection through direct observation, interviews, and documentation, concluded that the implementation of the singing method was highly effective in improving early reading skills in children aged 4-5 years. Evidenced by the use of the singing method, children listened to the alphabet song sung with enthusiasm, repeated the vowel and consonant sounds requested by the teacher, imitated the pronunciation of letters A to Z, increased their vocabulary for communication, and developed their speaking skills.